2019
DOI: 10.1111/jocd.12974
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the molecular and cellular mechanisms of stretch marks

Abstract: Background: Striae distensae, commonly known as stretch marks, are cutaneous lesions that accompany the hormonal upheavals of the major stages of life: puberty and pregnancy. Stretch marks occur in 90% of women, and they appear as red or purple lines that slowly fade to pale lines on the skin. There have been few studies regarding stretch mark origins, and new preventive and corrective treatments are needed. Aims: The aim of this work was to understand the primary genes and proteins involved in the regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
1
10
0
2
Order By: Relevance
“…1 Unlike normal skin, scar tissue exhibits characteristic features such as collagen fiber misalignment, excessive dermal fibrosis, and disruption of skin texture. 2,3 Dermal scarring can cause significant physical and psychological distress for patients, and treatment is inexact and complicated. [4][5][6] There remains a need for new methods to treat cutaneous scars beyond the current therapeutic armamentarium.…”
Section: Introductionmentioning
confidence: 99%
“…1 Unlike normal skin, scar tissue exhibits characteristic features such as collagen fiber misalignment, excessive dermal fibrosis, and disruption of skin texture. 2,3 Dermal scarring can cause significant physical and psychological distress for patients, and treatment is inexact and complicated. [4][5][6] There remains a need for new methods to treat cutaneous scars beyond the current therapeutic armamentarium.…”
Section: Introductionmentioning
confidence: 99%
“…The sample was representative of patients who seek care in dermatologic practice due to SD: Adult women who are overweight with intermediate phototypes and a high prevalence of familial SD. [27][28][29][30] While the population prevalence of SD is still unknown, the homogeneous distribution of SD among the breasts, abdomen, and buttocks Objective and reproducible measures to assess SD severity and compare the efficacy of therapies are valuable in clinical research and should be considered with other outcomes, such as quality of life and the subjective perception of the patient and the researcher. 4,[10][11][12][13][14][15][16][17]19,32,33 As a limitation of this study, the scale was not developed to assess acute (purple or red) SD or other body topographies (eg, lumbar, knee, or inner thigh).…”
Section: Discussionmentioning
confidence: 99%
“…The sample was representative of patients who seek care in dermatologic practice due to SD: Adult women who are overweight with intermediate phototypes and a high prevalence of familial SD 27‐30 . While the population prevalence of SD is still unknown, the homogeneous distribution of SD among the breasts, abdomen, and buttocks in this sample was crucial in developing a representative scale for these three areas.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the etiological mechanisms proposed relate to hormones and structural alterations to the integument 12 . Although etiological factors of striae distensae are not the same with SG, they may be considered as similar with etiological factors of SG 24 . We have provided the novel observation that women who have normal values of serum 25(OH)D have a lower risk of having SG than women who have scarce levels of serum 25(OH)D, even after adjustment for confounders.…”
Section: Discussionmentioning
confidence: 99%